Perovskite solar cell, preparation method and prepared laminated perovskite cell
By doping (3-(trifluoromethyl)benzyl)phosphonate diethyl phosphonate in the perovskite film layer and installing a modified material layer, the instability and inefficiency caused by defects in perovskite solar cells are solved. The problem has significantly improved the photoelectric conversion efficiency and stability of the battery.
Patent Information
- Application Number
- CN202411464354.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The instability and inefficiency of perovskite solar cells are mainly caused by non-radiative recombination and ion migration in the perovskite film layer, especially the concentration of defects at the surface and grain boundary positions, affecting the lifetime and efficiency of the device.
The perovskite film layer is doped with diethyl (3-(trifluoromethyl)benzyl)phosphonate, and a modified material layer is provided between the perovskite film layer and the electron transport layer, and the modified material has a suitable Ammonium root, forming a gradient p-type doping, improving the electron transport performance of perovskites.
By doping and modifying the material layer, the photoelectric conversion efficiency and stability of perovskite batteries are improved, the defect density is significantly reduced, and the service life of the device is extended.
Smart Images

Figure CN119300618A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a perovskite solar cell, a preparation method and a prepared laminated perovskite cell, and belongs to the photovoltaic field. Background Art
[0002] As a clean energy source, solar energy can meet the growing global energy demand. Among many optoelectronic devices, perovskite solar cells have attracted much attention due to their high photoelectric conversion efficiency and low manufacturing cost. The theoretical efficiency limit of a single-junction perovskite solar cell is about 31%, and the current laboratory record efficiency is 26.7%. According to the Photovoltaic Association, for every 1% increase in the absolute value of the efficiency of a photovoltaic cell, its levelized cost of electricity (LCOE) decreases by 5-7%. Therefore, improving the absolute efficiency of the cell is crucial to reducing costs in the photovoltaic industry.
[0003] Single-junction perovskite cells have achieved a photoelectric conversion efficiency of 26.7%, which is very close to the 27.3% efficiency of crystalline silicon. Further efficiency improvement is already very limited, and building tandem cells is a way to solve the above bottlenecks. Perovskite-crystalline silicon tandem cells (calcium silicon tandem cells) have received widespread attention due to their high conversion efficiency and compatibility. The efficiency and stability of the wide-bandgap perovskite cells in the calcium silicon tandem cells are still far from commercialization. Further improving the efficiency and stability of wide-bandgap cells is the focus of commercialization. Compared with the 20-30-year service life of crystalline silicon cells, the life of perovskites is generally believed to be within 5 years, and some literature estimates that the service life of perovskites is only 2-3 years. Under this service life, the levelized cost of electricity (LCOE) of the device will lag far behind commercial silicon cells. Therefore, improving the stability of perovskite cells is a top priority in promoting the commercialization of perovskite cells.
[0004] The sources of instability and low efficiency of perovskite cells are mainly non-radiative recombination and ion migration in the perovskite film layer. Among them, non-radiative recombination is dominated by defects. The presence of defects greatly increases the proportion of non-radiative recombination and significantly reduces the performance of the device; secondly, ion migration is the main factor leading to device degradation. For example, migrated halogen ions can react with electrodes and hinder the transmission of photogenerated carriers. Therefore, considering the above two aspects, defects inside perovskite devices are the most critical factor causing efficiency and stability degradation. According to research, perovskite defects are more concentrated on the surface and grain boundary positions of the perovskite film layer. In addition, the perovskite material itself is biased towards n-type crystals, which will produce a large potential barrier in the cross section in contact with the hole layer. The optimal situation for the perovskite film layer is that the lower interface in contact with the p-type transport layer is approximately p-type, and the upper interface in contact with the n-type transport layer is approximately n-type, thereby forming a more ideal pn junction, improving the efficiency of the built-in electric field and carrier separation and transmission, so the doping regulation of the perovskite film layer is one of the means to build high-performance devices. Summary of the invention
[0005] In order to improve the efficiency of the battery, the present invention provides a perovskite solar cell. The perovskite film layer is doped with (3-(trifluoromethyl)benzyl) diethyl phosphonate to convert the intrinsic weak n-type perovskite into p-type near the hole transport layer, and a modifying material is arranged between the perovskite film layer and the electron transport layer to convert the perovskite film layer near the electron transport layer into n-type, thereby improving the efficiency of the perovskite battery.
[0006] One of the schemes adopted is: a perovskite solar cell, comprising a substrate, a hole transport layer, a perovskite film layer, an electron transport layer and an electrode layer arranged in sequence to form a perovskite cell with a pin structure. The present invention provides a modification material layer between the perovskite film layer and the electron transport layer, the modification material layer has a suitable ammonium radical, can be closely connected to the surface, and form n-type doping with the perovskite film layer; the material of the perovskite film layer includes at least a perovskite material and an additive, an electron-withdrawing group is provided on the additive, so that the intrinsic perovskite material is converted into a p-type, and the distribution form of the additive on the perovskite film layer is: the content gradually decreases from close to the hole transport layer to close to the electron transport layer; this setting forms a gradient p-type doping inside the perovskite film layer, and presents a strong p-type characteristic on the hole transport layer side.
[0007] The modification material layer is arranged between the perovskite film layer and the electron transport layer material, so that the perovskite film layer close to the electron transport layer is n-type doped. On the basis of restoring the intrinsic weak n-type, the n-type characteristics are further strengthened, thereby improving the electron transport performance of the perovskite.
[0008] In the perovskite material ABX3 of the present invention, A is an organic-inorganic cation, B is a lead ion, and X is a halogen. The perovskite material can directly use the ABX3 material, or it can be two or more materials that can form ABX3 by reaction. As a preferred embodiment, A is a combination of one or more of formamidinium ions, methylamine ions, cesium ions, and rubidium ions, X is a combination of one or more of chloride ions, bromide ions, and iodide ions, and B is a lead ion. Preferably, the perovskite film material is composed of two or more components, and the two or more components are reacted to form an ABX3 type structural material, such as selecting a mixed solution of two or more of lead iodide, lead bromide, cesium iodide, rubidium iodide, formamidinium iodine, methylamine iodine, methylamine bromide, and methylamine chloride to form a deposition, and preferably the perovskite film material is selected from one or two of lead iodide and lead bromide, and one or more of cesium iodide, rubidium iodide, formamidinium iodine, methylamine iodine, methylamine bromide, and methylamine chloride, and react with each other to form.
[0009] As a preferred embodiment, the additive containing an electron-withdrawing group is diethyl (3-(trifluoromethyl)benzyl)phosphonate, and the structural formula is: ; This material not only contains groups such as P=O, has a strong ability to withdraw electrons, and has the potential to transform the intrinsic weak n-type of perovskite into p-type, but also can keep more content at the lower interface during the process of forming a perovskite film layer with the perovskite material. The various passivating functional groups in the material can effectively passivate the defects at the lower interface and reduce the defect density.
[0010] As a preferred embodiment, the material of the modified material layer is a combination of one or more of EDAI2 (ethane 1,2-diammonium iodide), CF3-PEAI (4-trifluoromethylphenethylamine iodide), PEAI (phenethylamine iodide), F-PEAI (p-fluorophenethylamine iodide), and CF3O-PEAI (4-trifluoromethoxyphenethylamine iodide). Further preferably, the thickness of the CF3O-PEAI modified material layer is 2~5nm. The modified film layer of this thickness can make the material have moderate conductivity. If it exceeds 5nm, transmission problems will occur, and if it is too thin, it will not play a doping role.
[0011] As a preferred embodiment, the hole transport layer material is a combination of one or more of MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid), Me-4PACz ((4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid), PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), and nickel oxide. The electron transport layer is a combination of one or more of fullerene and its derivatives, tin dioxide, and titanium dioxide.
[0012] The second solution adopted by the present invention is: a method for preparing a perovskite solar cell, comprising the following steps: S01 obtain substrate; S02 providing a hole transport layer on the substrate; S03 providing a perovskite film layer on the hole transport layer; S04 providing a modification material layer on the perovskite film layer; S05 providing an electron transport layer on the modification material layer; S06 providing an electrode layer on the electron transport layer; The method for preparing the hole transport layer is preferably: A. Mix MeO-PACz with ethanol solution to obtain MeO-2PACz ethanol solution, filter with a 0.45 μm filter element to remove large particles, and use the filtered solution for later use; B. Spin-coating the filtered solution on a substrate, preferably an ITO glass substrate; After annealing, a MeO-2PACz hole transport layer with a thickness of about 3 nm was obtained.
[0013] The preparation method of the perovskite film layer can be a solution method, a vacuum co-evaporation method, a vacuum and solution combination method, and the solution method includes a solution spin coating method, a solution scraping method, and a solution spraying method. The preferred preparation method is: a. Mix at least one component of lead iodide and lead bromide with at least one component of methylamine iodine, formamidine iodine, methylamine bromide, and methylamine chloride and an additive and deposit them on the hole transport layer, and the deposition method is one of spin coating, scraping, and spraying; b. Assisted crystallization film formation: the method is a combination of one or more of anti-solvent dripping, vacuum drying, and heating assistance; c. After the wet film is formed, heating annealing is performed to evaporate the residual solvent and promote the crystallization of the perovskite film layer; d. The thin film formed by annealing and crystallization is post-treated and dried by heating or vacuum.
[0014] Further preferably, the method for preparing the perovskite film layer comprises the following steps: A. PbI2, FAI, PbBr2, and FABr are dissolved in a mixture of N,N-dimethylformamide and dimethyl sulfoxide at a set molar ratio to form solution 1; B. Adding MACl to solution 1 to form solution 2; C. adding diethyl (3-(trifluoromethyl)benzyl)phosphonate to solution 2 to form solution 3; D. heating solution 3 and stirring until the solution is completely dissolved to obtain a perovskite film solution; E. filtering the perovskite film solution to obtain a filtrate, and spin-coating the filtrate on the hole transport layer, and adding anti-solvent chlorobenzene dropwise during the spin-coating process; F After spin coating, annealing is performed to obtain the perovskite film layer.
[0015] The preparation method of the modification material layer is as follows: a) dissolving the modification layer material in an organic solvent, wherein the organic solvent is one of toluene, chlorobenzene, methanol and ethanol; b) spin coating the modification layer solution on the perovskite film layer; c) heating the modified layer on a heating table and annealing the modified layer to solidify the modified layer. This preparation method can be applied to a variety of solvents, enhance the adjustability of the solvent, and select the appropriate solvent type according to the crystallization rate and mode of the modification layer material, so that the formed modification layer and the perovskite film layer are better integrated.
[0016] Further preferably, the method for preparing the modified material layer comprises the following steps: A. Dissolve CF3O-PEAI in isopropanol and chlorobenzene, and shake and stir until fully dissolved to form a modification layer material solution; B. Use the filter element to filter the modified layer material solution to obtain a filtrate; C. Spin-coat the filtered solution onto the perovskite film layer; D Annealing at 90~130℃ to obtain the modified material layer.
[0017] Based on the first and second solutions above, the perovskite cell prepared by the present invention is a wide bandgap perovskite cell, which can be used as a top cell of a stacked perovskite cell.
[0018] The beneficial effects of the present invention include: the present invention adds an additive material containing amino and acidic groups in the perovskite film layer, and the additive can remain in the film layer as the perovskite crystallizes. Since the molecule is easily deposited on the lower interface of the perovskite, the content decreases as the distance from the lower interface increases. This type of material has the following advantages: 1. The molecule contains groups such as P=O, which have a strong ability to absorb electrons and can convert the intrinsic weak n-type of the perovskite into a p-type; 2. The molecular structure contains a variety of passivating functional groups. Since a large amount of the content stays at the lower interface, that is, the interface in contact with the hole transport layer, a variety of groups can effectively passivate the lower interface and reduce the defect density; the present invention coats a layer of modifying material layer on the perovskite film layer, and the modifying material is EDAI2 and CF3O-PEAI. On the one hand, it can passivate the defects on the interface between the perovskite and the electron transport layer, and on the other hand, it can change the weak p-type on the interface to n-type, and work together with the additive to regulate the barrier of the perovskite and improve the efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Performance test diagram of the batteries obtained in Example 1 and Comparative Example 1 of the present invention; Figure 2 Performance side view of the batteries prepared in Example 2 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0020] The present invention will be further explained in detail below in conjunction with the accompanying drawings and specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Unless otherwise specified, any range recorded in the present invention includes any end value and any numerical value between the end values and any sub-range constituted by the end value or any numerical value between the end values. All raw materials of the present invention are not particularly limited to their purity, and the present invention preferably adopts analytical pure. All raw materials of the present invention, their sources and abbreviations all belong to conventional sources and abbreviations in this area, and are all clear and definite in the field of their related uses. Those skilled in the art can purchase or prepare them from commercially available according to the abbreviations and corresponding uses. All percentages of the present invention are mass percentages unless otherwise specified. Example
[0021] This embodiment prepares an inverted (pin) wide bandgap perovskite (1.67 eV) solar cell. The preparation method adopted is: S01 Get the base ITO glass was used as the substrate. The ITO glass substrate was first ultrasonically cleaned in a detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.
[0022] S02 Preparation of hole transport layer (1) Mix 1 mg of MeO-PACz with 1 mL of ethanol solution to obtain a 1 mg / mL MeO-2PACz solution, filter it with a 0.45 μm filter to remove large particles, and set the filtered solution aside; (2) Spin-coat the filtered solution on the ITO glass at a rate of 3300 rpm for 30 s. (3) Annealing at 120°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 3 nm.
[0023] S03 Preparation of perovskite film (1) Preparation of perovskite film solution a. PbI2 (lead iodide), FAI (methylamino iodide), PbBr2 (lead bromide), and FABr (methylamino bromide) were dissolved in a mixture of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) at a molar ratio of 0.75:0.75:0.25:0.25 to form a solution 1, wherein the volume ratio of DMF to DMSO was 5:1. 2+ The concentration is 1.7 mol / L; b. Add MACl (methylammonium chloride) additive to solution 1 to form solution 2. The mass fraction of MACl in solution 2 is 33.5%.
[0024] c. Add (3-(trifluoromethyl)benzyl)phosphonic acid diethyl ester additive to solution 2 to form solution 3. The mass fraction of (3-(trifluoromethyl)benzyl)phosphonic acid diethyl ester in solution 3 is 2%. The structural formula of (3-(trifluoromethyl)benzyl)phosphonic acid diethyl ester is: .
[0025] d. Heat the solution to 70°C and stir for 70 min until completely dissolved; e The solution is filtered using a 0.22 μm filter element to remove large particles in the solution to obtain a perovskite film solution.
[0026] (2) The perovskite film solution was spin-coated on the hole transport layer at a spin-coating rate of 4000 rpm. At the 30th second of spin-coating, 0.4 mL of anti-solvent chlorobenzene was dripped onto the film layer. After the dripping was completed within 4 seconds, the spin coating was continued for a total of 40 seconds.
[0027] (3) After spin coating, annealing was performed in air at 145°C for 20 min with humidity controlled at 20-30% to obtain a perovskite film with a thickness of about 700 nm.
[0028] S04 Preparation of modified material layer (1) Prepare the modification layer solution by dissolving 0.6 mg of CF3O-PEAI in 0.5 mL of isopropanol and 0.5 mL of chlorobenzene, shaking and stirring to form a 0.6 mg / mL solution, and filtering with a 0.45 μm filter to remove larger particles in the solution.
[0029] (2) The modification layer solution was spin-coated on the perovskite film layer at a speed of 2000 rpm for 30 s, and then annealed in a glove box at 100 °C for 3 min using a heating table to form a modification layer with a thickness of about 5 nm.
[0030] S05 Preparation of electron transport layer Using vacuum evaporation equipment, C is evaporated by thermal evaporation. 60 Materials, forming a 20nm electron transport layer on the perovskite film layer, the evaporation vacuum degree is 7*10 -4 Below Pa.
[0031] Preparation of S06 hole blocking layer: Vacuum evaporation equipment was used to evaporate BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or bathocuproin) material by thermal evaporation to form an 8nm hole blocking layer on the electron transport layer. The evaporation vacuum was 7*10 -4Below Pa.
[0032] Preparation of S07 electrode: Using vacuum evaporation equipment, 150nm copper (Cu) was evaporated on the surface of BCP by thermal evaporation as an electrode. The vacuum degree of evaporation was 7*10 -4 Below Pa.
[0033] Comparative Example 1 The only difference from Example 1 is that diethyl (3-(trifluoromethyl)benzyl)phosphonate is not added to the perovskite film layer, and a modification material layer is not provided between the perovskite film layer and the electron transport layer.
[0034] The photoelectric conversion efficiency of the perovskite solar cells of Example 1 and Comparative Example 1 was tested by scanning from high voltage (1.3V) to low voltage (-0.1V), with a scanning step of 0.1V and an interval of 20ms. The conversion power of the cell was obtained by multiplying the voltage and current, and the conversion efficiency of the cell was obtained by combining the incident power of sunlight. Figure 1 It can be seen that the conversion efficiency of the perovskite solar cell in Example 1 is significantly improved compared with that in Comparative Example 1. In particular, the FF (fill factor) is 71.2% when no modification layer is added, and is increased to 78.0% after adding the modification layer, indicating that pn doping effectively accelerates carrier transport. Example
[0035] This embodiment prepares an inverted (pin) wide bandgap perovskite (1.67 eV) solar cell. The preparation method adopted includes the following steps: S01 Get the base ITO glass was used as the substrate. The ITO glass substrate was first ultrasonically cleaned in a detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.
[0036] S02 Preparation of hole transport layer (1) Mix 1 mg of MeO-PACz with 1 mL of ethanol solution to obtain a 1 mg / mL MeO-2PACz solution, filter it with a 0.45 μm filter to remove large particles, and set the filtered solution aside; (2) Spin-coat the filtered solution on the ITO glass at a rate of 3300 rpm for 30 s. (3) Annealing at 120°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 3 nm.
[0037] S03 Preparation of perovskite film (1) Preparation of perovskite film solution a. PbI2 (lead iodide), FAI (methylamino iodide), PbBr2 (lead bromide), and FABr (methylamino bromide) were dissolved in a mixture of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) at a molar ratio of 0.75:0.75:0.25:0.25 to form a solution 1, wherein the volume ratio of DMF to DMSO was 5:1. 2+ The concentration is 1.7 mol / L; b. Add MACl additive to solution 1 to form solution 2, and the mass fraction of MACl in solution 2 is 33.5%; c. Add (3-(trifluoromethyl)benzyl)phosphonic acid diethyl ester additive to solution 2 to form solution 3. The amount of (3-(trifluoromethyl)benzyl)phosphonic acid diethyl ester added to solution 3 is 4%; the structural formula of (3-(trifluoromethyl)benzyl)phosphonic acid diethyl ester is: .
[0038] d. Heat the solution to 70°C and stir for 70 min until completely dissolved; e The solution is filtered using a 0.22 μm filter element to remove large particles in the solution to obtain a perovskite film solution.
[0039] (2) The perovskite film solution was spin-coated on the hole transport layer at a spin-coating rate of 4000 rpm. At the 30th second of spin-coating, 0.4 mL of anti-solvent chlorobenzene was dripped onto the film layer. After the dripping was completed within 4 seconds, the spin coating was continued for a total of 40 seconds.
[0040] (3) After spin coating, annealing was performed in air at 145°C for 20 min with humidity controlled at 20-30% to obtain a perovskite film with a thickness of about 700 nm.
[0041] S04 Preparation of modified material layer (1) Prepare a solution for the modified material layer by dissolving 0.3 mg of EDAI2 in 1.0 mL of isopropanol, shaking and stirring to form a 0.3 mg / mL solution, and filter using a 0.45 μm filter to remove larger particles in the solution.
[0042] (2) The modification material layer solution was spin-coated on the perovskite film layer at a speed of 2000 rpm for 30 s, and then annealed in a glove box at 100 °C for 5 min using a heating table to form a modification material layer with a thickness of about 3 nm.
[0043] S05 Preparation of electron transport layer Using vacuum evaporation equipment, C is evaporated by thermal evaporation. 60Materials, forming a 20nm electron transport layer on the perovskite film layer, the evaporation vacuum degree is 7*10 -4 Below Pa.
[0044] Preparation of S06 hole blocking layer: Using vacuum evaporation equipment and atomic layer deposition equipment, a 20nm SnOx layer is formed on the electron transport layer. The vacuum degree of evaporation is 6*10 -4 Below Pa.
[0045] Preparation of S07 electrode: Using vacuum evaporation equipment, 150nm silver (Ag) was evaporated on the surface of SnOx by thermal evaporation as an electrode. The vacuum degree of evaporation was 7*10 -4 Below Pa; A perovskite solar cell was produced.
[0046] Comparative Example 2 The differences from Example 2 are that (1) diethyl (3-(trifluoromethyl)benzyl)phosphonate is not added to the perovskite film layer, and (2) a modifying material layer is not provided between the perovskite film layer and the electron transport layer.
[0047] The photoelectric conversion efficiency of the perovskite solar cells of Example 2 and Comparative Example 2 was tested by scanning from high voltage (1.3V) to low voltage (-0.1V), with a scanning step of 0.1V and an interval of 20ms. The conversion power of the cell was obtained by multiplying the voltage and current, and the conversion efficiency of the cell was obtained by combining the incident power of sunlight. Figure 2 It can be seen that the conversion efficiency of the perovskite solar cell in Example 2 is significantly improved compared with that in Comparative Example 2. After adding the modified layer in Example 2, the filling factor FF is 78.4%, which is significantly improved compared with the filling factor of 72.1% in Comparative Example 2, which further indicates that pn doping effectively accelerates carrier transport.
[0048] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A perovskite solar cell, comprising a substrate, a hole transport layer, a perovskite film layer, an electron transport layer and an electrode layer, characterized in that: The perovskite film layer includes a perovskite material ABX3 and an additive, wherein A is an organic-inorganic cation, B is a lead ion, and X is a halogen. The additive contains an electron-withdrawing group. The additive is mixed with the perovskite material to form the perovskite film layer. A modification material layer is arranged between the perovskite film layer and the electron transport layer. The modification material layer forms n-type doping on the contact interface of the perovskite film layer.
2. The perovskite solar cell according to claim 1, characterized in that: The material in the modified material layer is a combination of one or more of EDAI2, CF3O-PEAI, CF3-PEAI, PEAI, and F-PEAI.
3. The perovskite solar cell according to claim 1 or 2, characterized in that: The additive is diethyl (3-(trifluoromethyl)benzyl)phosphonate, and the structural formula is: 。 4. The perovskite solar cell according to claim 1, characterized in that: In the perovskite material ABX3 in the perovskite film layer, A is a combination of one or more of formamidinium ions, methylamine ions, cesium ions, and rubidium ions, X is a combination of one or more of chloride ions, bromide ions, and iodine ions, and B is a lead ion.
5. The perovskite solar cell according to claim 1, characterized in that: The content of the additive in the perovskite film layer gradually decreases from the side close to the hole transport layer to the side close to the electron transport layer.
6. A method for preparing a perovskite solar cell, characterized in that: The following steps are involved: S01 obtain substrate; S02 preparing a hole transport layer on a substrate; S03 preparing a perovskite film layer on the hole transport layer, wherein the perovskite film layer is a mixed material layer of the perovskite material ABX3 and an additive, wherein the additive contains an electron-withdrawing group; S04 preparing a modification material layer on the perovskite film layer, wherein an n-type doping is formed on a contact interface between the modification material and the perovskite film layer; S05: preparing an electron transport layer on the modified material layer.
7. The method for preparing a perovskite solar cell according to claim 6, characterized in that: The method for preparing the perovskite film layer comprises the following steps A. PbI2, FAI, PbBr2, and FABr are dissolved in a mixture of N,N-dimethylformamide and dimethyl sulfoxide at a set molar ratio to form solution 1; B. Adding MACl to solution 1 to form solution 2; C. adding diethyl (3-(trifluoromethyl)benzyl)phosphonate to solution 2 to form solution 3; D. heating solution 3 and stirring until the solution is completely dissolved to obtain a perovskite film solution; E. filtering the perovskite film solution to obtain a filtrate, and spin-coating the filtrate on the hole transport layer, and adding anti-solvent chlorobenzene dropwise during the spin-coating process; F After spin coating, annealing is performed to obtain the perovskite film layer.
8. The method for preparing a perovskite solar cell according to claim 6, characterized in that: The mass concentration of diethyl (3-(trifluoromethyl)benzyl)phosphonate in solution three is 1% to 5%.
9. The method for preparing a perovskite solar cell according to claim 6, characterized in that: The material in the modified material layer is CF3O-PEAI, and the preparation method of the modified material layer is: A. Dissolve CF3O-PEAI in isopropanol and chlorobenzene, and shake and stir until fully dissolved to form a modification layer material solution; B. Use the filter element to filter the modified layer material solution to obtain a filtrate; C. Spin-coat the filtered solution onto the perovskite film layer; D Annealing at 90~130℃ to obtain the modified material layer.
10. A perovskite tandem solar cell, characterized in that: The wide bandgap cell is prepared by using the perovskite solar cell described in any one of claims 1 to 5 or the perovskite solar cell prepared by the preparation method described in any one of claims 6 to 9.
Citation Information
Patent Citations
Preparation method of perovskite solar cell
CN113707816A
Inverse perovskite solar cell and preparation method thereof
CN116669444A
Inverse perovskite solar cell and preparation method thereof
CN116782681A
Passivation layer modified trans-perovskite solar cell and preparation method thereof
CN117998878A
Perovskite solar cell and preparation method thereof
CN118338693A
Cited By
Perovskite battery containing multiple modification layers and preparation method thereof
CN120692993A
Perovskite precursor solution additive, solution, solar cell and preparation method
CN120711986A